EVALUASI TAJAM PENGLIHATAN DAN INDEKS PROPTOSIS PASIEN MENINGIOMA SPHENOORBITA PASCAOPERASI KRANIEKTOMI - Renindra Ananda Aman; Ryan Rhiveldi Keswani; Syaiful Ichwan; Samsul Ashari; Setyo Widi Nugroho (PERDOSNI, 2020)
Introduction: Sphenoorbital meningioma (SOM) is an exophytic tumor mass that infiltrates the bone at the sphenoid wing, lateral orbital walls, orbital roofs, and extends to superior orbital fissures. The classic triad of clinical features are proptosis, decreased visual acuity, and ophthalmoplegia. The outcomes of our postoperative patients have not been evaluated before. Aim: We would like to evaluate the clinical characteristics of the sphenoorbital menigioma patients before and after surgery. Methods: A cross sectional study was performed. Subjects were patients with sphenoorbital meningiomas who came to Cipto Mangunkusumo General Hospital from January 2014 through December 2015. All patients underwent craniectomy and lateral orbitotomy. We evaluated the visual acuity using the Snellen chart and proptosis index before and after surgery by measuring the protuded eye in an axial CT scan. Results: There were 66 samples in this study, and 65 of the samples were females. The age range is from 31 to 64 years. The mean proptosis index of preoperative is 18.27 and the post operative is 16.43. The mean proptosis index reduction is 1.84. Post operative visual acuity was improved only in 3 (9.7%) samples. Discussion: Sphenoorbital meningioma patients after surgery were shown markedly improvement in the proptosis index. However, the visual acuity was not markedly improved after surgery. Keywords: Proptosis index, sphenoorbital meningioma, visual acuity